Theory of Transformational Leadership towards Employee Performance as Sequence of Supply Chain Model: The Mediating Effect of Job Autonomy in Palestine Banks during COVID-19 Pandemic - Alkadash, Tamer; Almaamari, Qais; Al-Absy, Mujeeb Saif; Raju, Valliappan (International Journal of Supply Chain Management, 2020)
This research aims to establish the relationship between transformation leadership and employee performance among staff in Palestine banks similar to any Supply Chain Management model, literature to describe the transformational leadership with the relationship with employee performance and job autonomy. The study tool-type quantitative research via questionnaire method was utilized to collect the data from respondents, structural equation modeling using SPSS V20 run to test the research hypothesis. The result indicates that the positive relationship between transformational leadership and employee performance among employees in the bank sector, Job autonomy also has a partial meditate on the relationship between transformational leadership and employee performance. This study 's greatest drawback is its low sample size. This enabled the authors to bring Supply Chain model. Despite this, the results cannot be generalized to the entire high-bank population; the size of the data set used also restricted the study's scope.  The sample (N=311) was made up. The main findings were related to confirming the two main hypotheses of the research that were related to testing if there were relationships between transformational leadership and employee performance via job autonomy as a mediator, the study may help the management of banks to develop an understanding of the value of transformational leadership that would enhance employee performance. The study explores the important issue and calls for more research in this domain. The paper adds value between transition leadership, employee productivity, and work flexibility to the organization's small knowledge base. The results presented in this paper would aid Palestinian academics, leadership experts, supply chain management professionals and organizational scientists in improving the efficiency of employees there through transformative leadership. Mediation research was carried out using special statistical methods.